Accelerated pre‐senile systemic amyloidosis in PACAP knockout mice – a protective role of PACAP in age‐related degenerative processes. Issue 4 (4th July 2018) - Reglodi, Dora; Jungling, Adel; Longuespée, Rémi; Kriegsmann, Joerg; Casadonte, Rita; Kriegsmann, Mark; Juhasz, Tamas; Bardosi, Sebastian; Tamas, Andrea; Fulop, Balazs Daniel; Kovacs, Krisztina; Nagy, Zsuzsanna; et al.
Abstract: Dysregulation of neuropeptides may play an important role in aging‐induced impairments. Among them, pituitary adenylate cyclase‐activating polypeptide (PACAP) is a potent cytoprotective peptide that provides an endogenous control against a variety of tissue‐damaging stimuli. We hypothesized that the progressive decline of PACAP throughout life and the well‐known general cytoprotective effects of PACAP lead to age‐related pathophysiological changes in PACAP deficiency, supported by the increased vulnerability to various stressors of animals partially or totally lacking PACAP. Using young and aging CD1 PACAP knockout (KO) and wild type (WT) mice, we demonstrated pre‐senile amyloidosis in young PACAP KO animals and showed that senile amyloidosis appeared accelerated, more generalized, more severe, and affected more individuals. Histopathology showed age‐related systemic amyloidosis with mainly kidney, spleen, liver, skin, thyroid, intestinal, tracheal, and esophageal involvement. Mass spectrometry‐based proteomic analysis, reconfirmed with immunohistochemistry, revealed that apolipoprotein‐AIV was the main amyloid protein in the deposits together with several accompanying proteins. Although the local amyloidogenic protein expression was disturbed in KO animals, no difference was found in laboratory lipid parameters, suggesting a complex pathway leading to increased age‐related degeneration with amyloid deposits in the absence of PACAP. In spite of no marked inflammatory histological changes or blood test parameters, we detected a disturbed cytokine profile that possibly creates a pro‐inflammatory milieu favoring amyloid deposition. In summary, here we describe accelerated systemic senile amyloidosis in PACAP gene‐deficient mice, which might indicate an early aging phenomenon in this mouse strain. Thus, PACAP KO mice could serve as a model of accelerated aging with human relevance. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.